2013
DOI: 10.1021/ic400945u
|View full text |Cite
|
Sign up to set email alerts
|

New Media for Classical Coordination Chemistry: Phase Transfer of Werner and Related Polycations into Highly Nonpolar Fluorous Solvents

Abstract: Optimized procedures for the previously reported conversions of 1,3-diiodobenzene and perfluorohexyliodide (Rf6I; copper, DMSO, 140 °C) to 1,3-C6H4(Rf6)2 (3; 86-70%) and 3 to Br(3,5-C6H3(Rf6)2 (2; NBS, H2SO4/CF3CO2H; 88-75%) are described. The latter is converted (t-BuLi, BCl3) to the "fluorous BArf" salt NaB(3,5-C6H3(Rf6)2)4 (1 or NaBArf6; 77-70%), as given earlier. When orange aqueous solutions of [Co(en)3]Cl3 (en = ethylenediamine) are treated with perfluoro(methylcyclohexane) (PFMC) solutions of 1 (1:3 mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…8 Not surprisingly, coordination compounds can function similarly, and frequently offer architectures and binding site arrays that have no counterparts in organic systems. Another has been the development of lipophilic 4 and/or fluorophilic 9 Werner complexes, such that catalysis can be conducted in the absence of water, which would otherwise saturate (or compete with substrate access to) the hydrogen bond donor sites. environments, and it is left to motivated readers to derive the extensive families of stereoisomers that can result.…”
Section: Introductionmentioning
confidence: 99%
“…8 Not surprisingly, coordination compounds can function similarly, and frequently offer architectures and binding site arrays that have no counterparts in organic systems. Another has been the development of lipophilic 4 and/or fluorophilic 9 Werner complexes, such that catalysis can be conducted in the absence of water, which would otherwise saturate (or compete with substrate access to) the hydrogen bond donor sites. environments, and it is left to motivated readers to derive the extensive families of stereoisomers that can result.…”
Section: Introductionmentioning
confidence: 99%
“…Work-up gave the target compound 1,3-R f6 C 6 H 4 I in 60% yield (based upon limiting R f6 I). Some of the previously reported dialkylation product 1,3-(R f6 ) 2 C 6 H 4 was also formed [ 47 48 ], but was easily separated due to its differential fluorophilicity (extraction of a CH 3 CN solution with perfluorohexane). An analogous procedure with R f10 I gave the higher homolog 1,3-R f10 C 6 H 4 I in 50% yield [ 9 ], and a lesser amount of what was presumed to be the dialkylation product.…”
Section: Resultsmentioning
confidence: 97%
“…Syntheses and reactions, aryl iodides with two perfluoroalkyl groups. In a previously reported procedure [ 48 ], the diiodide 1,3-C 6 H 4 I 2 was treated with copper (5.1 equiv) and R f6 I (2.2 equiv) in DMSO at 140 °C. As shown in Scheme 6 (top), the bis(perfluorohexyl) adduct 1,3-(R f6 ) 2 C 6 H 4 , which was the undesired byproduct in Scheme 5 (top), was isolated in 75% yield.…”
Section: Resultsmentioning
confidence: 99%
“…The doubly fluorous salts (14,15) gave satisfactory microanalyses. However, the carbon values of other salts were slightly off (0.67-0.70% for 4 and 9), and in two cases the sulfur values similarly deviated (12,16).…”
Section: Properties Of Fluorous Iron/sulfur Clustersmentioning
confidence: 96%
“…11 Horváth, Rábai, our group, and many others have demonstrated that by introducing appropriate numbers of perfluoroalkyl groups ((CF 2 ) n−1 CF 3 = R fn ) of sufficient lengths, a variety of neutral molecules can be rendered soluble in nonpolar fluorous liquid phases, such as perfluorohexanes . 12 We have also shown that many ionic compounds, 13 such as organic ammonium and phosphonium salts, as well as salts of inorganic polycations, 14 can similarly be rendered soluble in fluorous phases. 15,16 As such, it was natural to speculate whether the right combination of fluorous thiolate substituents and fluorous cations might render salts of the type nQ + [Fe 4 S 4 (SR) 4 ] n− soluble in fluorous media.…”
Section: Introductionmentioning
confidence: 96%